Loop-mediated isothermal amplification (LAMP)/Cas12a assay for detection of Ralstonia solanacearum in tomato - Fan, Zhiyu; Mei, Yuxia; Xing, Jiawei; Chen, Tian; Hu, Di; Liu, Hui; Li, Yingjun; Liu, Derui; Liu, Zufeng; Liang, Yunxiang (Frontiers in Bioengineering and Biotechnology, 2023)
Bacterial wilt (BW) caused by the aerobic, Gram-negative pathogenic species Ralstonia solanacearum (RS) is a major disease impacting commercial agriculture worldwide. Asian phylotype I of RS is the cause of tomato bacterial wilt, which has caused severe economic losses in southern China for many years. An urgent priority in control of bacterial wilt is development of rapid, sensitive, effective methods for detection of RS. We describe here a novel RS detection assay based on combination of loop-mediated isothermal amplification (LAMP) and CRISPR/Cas12a. crRNA1, with high trans-cleavage activity targeting hrpB gene, was selected out of four candidate crRNAs. Two visual detection techniques, involving naked-eye observation of fluorescence and lateral flow strips, were tested and displayed high sensitivity and strong specificity. The LAMP/Cas12a assay accurately detected RS phylotype Ⅰ in 14 test strains, and showed low detection limit (2.0×100 copies). RS in tomato stem tissue and soil samples from two field sites with suspected BW infection was identified accurately, suggesting potential application of LAMP/Cas12a assay as point-of-care test (POCT). The overall detection process took less than 2 h and did not require professional lab equipment. Our findings, taken together, indicate that LAMP/Cas12a assay can be developed as an effective, inexpensive technique for field detection and monitoring of RS.